Woman wearing YWCA blue ribbon - Unknown:::Creator::::::::::::
Photograph shows a nicely dressed woman seated outdoors. She is wearing a name tag that says: "visitor" and a blue ribbon that reads: " YWCA [illegible]." Her hands are folded and her purse is in her lap.